An overview of the Afrotropical Ommatiinae (Diptera: Asilidae) with a key to genera - Scarbrough, A. G. (Zootaxa, 2010)
The nine genera of the Afrotropical Ommatiinae are briefly reviewed and include a revised key to genera. A new genus and a species group are diagnosed and described. New genus: Longibeccus (type species, O. fuscovittatus Ricardo, 1900). New combinations: Transferred to Longibeccus from Ommatius, 1821: O. fuscovittatus Ricardo, 1900, and O. imperator Oldroyd, 1939. New status: subgenus Metommatius Hull, 1962, is elevated to generic level. New species group: neotenellus includes Ommatius coperitus n. sp., O. latus n. sp., O. neotenellus Bromley, O. polixus n. sp., and O. ultimus n. sp. from east Africa. The male of O. neotenellus is described for the first time. Only one species of Michotamia (M. coarctata Macquart, 1855), is confirmed from Madagascar. New synonymies: Afroestricus minutus (Bromley 1936)=Ommatius flavipes Loew, 1860; Michotamia cothurnata (Bigot, 1875)=Cophinopoda pulchripes (Bigot,1859). Illustrations of heads, antennae, wings, and terminalia of selected species and keys to the species of Longibeccus and the neotenellus group are provided. Distributions of the Afrotropical genera are briefly discussed.